Workloads and burnout of nursing workers - Deciane Pintanela de Carvalho; Laurelize Pereira Rocha; Eliana Cardia de Pinho; Jamila Geri Tomaschewski-Barlem; Edison Luiz Devos Barlem; Leonardo Salomão Goulart (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to identify workloads in nursing work and its association with nursing worker burnout. Method: a cross-sectional study, including 211 nursing workers from a university hospital, between July and August 2016. For the analysis, the descriptive statistics, Chi-Square Test, Fisher's Exact Test and Mann Whitney U-Test were used. Results: the most evidenced loads were biological. A significant association was found between workloads and workers' occupation, as well as a significant association between workloads and worker burnout. Burnout caused upper limb pain, neck and lumbar pain, lower limb pain, muscle spasm, lower limb edema, mental fatigue, headache, nervousness, and forgetfulness. Conclusion: workloads identification is a subsidy for the promotion of interventions that minimize the burnout generated to the health of the nursing worker.